Peran Environmental Knowledge dan Green Consumption dalam Memediasi Hubungan antara Green Marketing dan Green Buying Behavior di Wisata Rumah Atsiri Indonesia - Zakiyah, Nadiya Fikriyatuz; Rahadhini, Marjam Desma; Noviani, Siska; Aroran, Farryl Febian (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Environmental awareness has driven the rise of green consumption behavior. This study aims to examine the influence of green marketing on green buying behavior at Rumah Atsiri Indonesia, with environmental knowledge and green consumption as mediating variables. A quantitative approach was employed using Structural Equation Modeling (SEM). A total 200 respondents were selected through purposive sampling targeting visitors who have experienced eco-friendly product consumption at the tourism site. The findings reveal that green marketing-represented by ecolabeling, green advertising, and green branding-has a significant effect on green buying behavior both directly and indirectly through environmental knowledge and green consumption. These results highlight the crucial role of environmental awareness and green consumption in strengthening the link between green marketing strategies and consumer purchasing behavior.